2015
DOI: 10.1371/journal.pone.0120301
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Levels of Oxygen Stimulate Intimal Hyperplasia in Human Saphenous Veins via a ROS-Dependent Mechanism

Abstract: Saphenous veins used as arterial grafts are exposed to arterial levels of oxygen partial pressure (pO2), which are much greater than what they experience in their native environment. The object of this study is to determine the impact of exposing human saphenous veins to arterial pO2. Saphenous veins and left internal mammary arteries from consenting patients undergoing coronary artery bypass grafting were cultured ex vivo for 2 weeks in the presence of arterial or venous pO2 using an established organ culture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…HSVECs were maintained in ECM medium supplemented with 25 ml of fetal bovine serum (FBS), 5 ml of endothelial cell growth supplement and 5 ml of penicillin/streptomycin solution. HSVSMCs were obtained by the explant method as previously described [ 53 ]. The VSMC phenotype was confirmed by the typical “hill and valley” growth pattern in culture and by immunofluorescence staining using antibodies against α-smooth-muscle actin (α-SMA).…”
Section: Methodsmentioning
confidence: 99%
“…HSVECs were maintained in ECM medium supplemented with 25 ml of fetal bovine serum (FBS), 5 ml of endothelial cell growth supplement and 5 ml of penicillin/streptomycin solution. HSVSMCs were obtained by the explant method as previously described [ 53 ]. The VSMC phenotype was confirmed by the typical “hill and valley” growth pattern in culture and by immunofluorescence staining using antibodies against α-smooth-muscle actin (α-SMA).…”
Section: Methodsmentioning
confidence: 99%
“…In order to establish GO’s role in modulating inflammatory responses if any, reactive oxygen species (ROS) expression in SHSY-5Y cells cultured atop GO-coated meshes was analyzed using immunofluorescence following published procedures (65). Levels of ROS in SHSY-5Y cultured in the vicinity of GO-coated surfaces were assessed using conversion of non-fluorescent dihydroethidium (DHE:Sigma) to fluorescent ethidium bromide.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, it is suggested that stripping of varicose hSV reduces local production of harmful reactive oxygen metabolites (ROM) resulting in a positive effect on vein physiology (Flore et al 2003 ). Furthermore, according to Joddar et al ( 2015 ), the higher arterial levels of oxygen and elevated level of reactive oxygen species (ROS) stimulates intimal hyperplasia in hSV organ culture models where the hSVs were harvested by standard endovascular techniques. However, data from such in vitro organ culture studies (14 days in the medium, changed every 2 days; some culture medium also containing compound tiron to help reoxygenation) may be limited and may not reflect the true physiological events that occur in vivo hSV when used in CABG patients.…”
Section: Vasa Vasorum and Hypoxiamentioning
confidence: 99%